PERANCANGAN DAN PEMBUATAN OTOMATISASI PADA ALAT PENGERINGAN SALE PISANG BERBASIS MIKROKONTROLER RENESAS R8C/13 - Luluk Masruroh, Farid Samsu H, (Jurnal Neutrino, 2008)
Dried banana chip was kinds of food made from banana that dried to certain level of water contain. Generally, drying process use heat of sun as natural drying. Natural drying exactly economical, because didn’t need many instrumentation and costs, but it is depend on nature. However, drying product less hygienic because susceptible concerning manure and growing microorganism. Beside that, drying can only be effective at dry season with necessity time about one week. This design make automation on drying system dried banana chips using microcontroller R8C/13 where automation be located at temperature control maintain stability temperature of drying room and mass control in order to maintain mass dried banana chips don’t excess setting mass determined before. Stability of room temperature and the controlled mass dried banana chips indicate the existence of control balance. This instrument automatically work began with starting heater to increase temperature in the drying room, temperature sensor (LM35) detect temperature in drying room and starting mass sensor detect mass of banana and convert it to voltage. While temperature in drier room not quite (less from) 50oC, heater will switch on. And if temperature more than or same with 50oC, so heater switch off and fan switch on. Drying process will finish if mass of banana has achieved set point determined before. This instrument has been tried to dry banana 400 gram need drying time about 12 hours. This instrument can dry banana so that the weight decrease to 20% of initial mass.